SCHOOL ADMINISTRATIVE SYSTEM WITH MONEY PAYMENT PROCESS COMPUTERIZED - Tri Cahyati; Jalinas, SKom., MM (Jurnal Sistem Informasi, 2003)
In this paper the author explores the heading "Tuition Payments Administration System with Computerized Process." The principal issues to be discussed is the system of school administration concerning the payment of fees at the Junior High School 20 in kompurisasikan. In this writing consists of understanding the system, Data Flow Diagram, which consists of the ERD concept, the concept of normalization. Then the design of systems that consist of context diagram, diagram of zero, Entity Relationship Diagrams, ERD to a relational database transformation and normalization. School administration system that the authors put forward is used to accelerate the payment of fees and the creation of efficiency and effectiveness of the work on the administration to support the smooth process of teaching and learning in Junior High School 20.